PENGGUNAAN TEKNOLOGI INFORMASI MEMODERASI PENGARUH LOCUS OF CONTROL DAN EFEKTIVITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN - Ni Kadek Dwi Marina; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2021)
Employee performance is the work achieved by an employee in carrying out tasks in accordance with the responsibilities assigned to him. Factors that can affect performance are Locus Of Control, how effective the application of Accounting Information Systems (SIA) is, and the use of Information Technology (IT). The purpose of this research is to determine the effect of the Use of Information Technology on the relationship between Locus of Control, Effectiveness of Accounting Information Systems and Employee Performance. This research was conducted in 25 BPRs in Gianyar Regency, with a total of 60 people as the sample. The sampling technique is sampling and is calculated using the Slovin formula. Descriptive analysis was used to analyze the data through: validity test, reliability test, classical assumption test, MRA, F test, coefficient of determination (R2), and t test. The findings of this study are: (1) Locus of Control has a positive effect on employee performance, with a regression coefficient of 0.142 and a tcount of 1.974 with a significance value (Sig.) Of 0.034 <0.05. (2) The effectiveness of AIS has a positive effect on employee performance, the regression coefficient is 0.252 and the tcount is 2.495 with a significance value (Sig.) Of 0.001 <0.05. (3) The use of Information Technology is non-moderating in the relationship between Locus of Control and Employee Performance, with a regression coefficient of -0.159 and a tcount of -1.075 with a significant value (Sig.) Of 0.287> 0.05. (4) The relationship between AIS effectiveness and employee performance is not moderated by the use of information technology, with a regression coefficient of 0.118 and a tcount of 0.792 with a significance value (Sig.) Of 0.432> 0.05.